1993
DOI: 10.1111/j.1365-2958.1993.tb01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐dependent stability of the ferredoxin I transcripts from the cyanobacterial strains Synechococcus species PCC 7942 and Anabaena species PCC 7937

Abstract: The effect of iron on ferredoxin I specific mRNA levels was studied in the cyanobacterial strains Synechococcus sp. PCC 7942 (Anacystis nidulans R2) and Anabaena sp. PCC 7937 (Anabaena variabilis ATCC 29413). In both strains addition of iron to iron-limited cells resulted in a rapid increase in ferredoxin mRNA levels. To investigate the possible role of the ferredoxin promoter in iron regulation, a vector for promoter analysis in Synechococcus PCC 7942 strain R2-PIM9 was constructed, which contains the ferredo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Flavodoxin mRNA increases when iron is removed, but the ferredoxin mRNA level does not change. Ferredoxin protein, however, turns over rapidly in low iron medium (29).…”
Section: Discussionmentioning
confidence: 99%
“…Flavodoxin mRNA increases when iron is removed, but the ferredoxin mRNA level does not change. Ferredoxin protein, however, turns over rapidly in low iron medium (29).…”
Section: Discussionmentioning
confidence: 99%
“…Bovy et al (1993b) reported that the half life of Synechococcus ferredoxin I mRNA is greater in the presente of abundant iron. Both the 5' untranslated region and the first part of the coding region are required for this response (Bovy et al, 1993a), just as they are for the Fed-7 light response (Dickey et al, 1992b).…”
Section: Dlscusslonmentioning
confidence: 99%
“…For example, the stabilities of ompA mRNA in Escherichia coli and aprE mRNA in Bacillus subtilis are regulated according to growth stage and growth rate, respectively (Emory and Belasco, 1990;Resnekov, 1990), endonucleolytic cleavage within the puf mRNA in Rhodobacter capsulatus is regulated by oxygen (Klug, 1991), and the ferredoxin I transcripts in Synechococcus are stabilized in the presence of iron (Bovy et al, 1993). Potential determinants of mRNA stability include both the 5Ј and 3Ј ends of the transcript, endonucleolytic sites within the transcript, and, in some cases, translation (reviewed in Brawerman, 1987;Cohen, 1995).…”
Section: Introductionmentioning
confidence: 99%